CONTRIBUTION TO THE KNOWLEDGE OF ODONATA (INSECTA) IN MOLDOVA: IAŞI COUNTY - Martin Lemke (Journal of Experimental and Molecular Biology)
From 21‑vi to 29‑vi‑2024 I made an odonatological study trip to Iaşi County, northeastern Romania. During this trip I examined 39 sites of both standing and flowing water and noticed 23 species of Odonata. Many sites are threatened by littering and drying out. The results of the trip demonstrate the summer aspect of the Southeast European dragonfly and damselfly fauna; neither spring nor autumn species were observed. Interesting from a faunistic point of view are the very early observation of immature Sympecma fusca at two sites, the northernmost record of Somatochlora meridionalis east of the Carpathians, and the almost complete absence of species of the genera Lestes, Aeshna, Gomphus s.l., Libellula and Sympetrum. The mentions of some species in the literature are critically examined.